Edukasi Pencegahan dan Penyalahgunaan Narkoba Bagi Anak dan Remaja di Desa Dumolodo dan Desa Ipilo Kecamatan Gentuma Raya - Rawiyah Husnan; Frice L Desei (Univeristas Negeri Gorontalo, 2022)
In this modern and sophisticated era, drugs have become a problem for many people across the globe. Drugs can spoil our mind, harm our body and soul, and inevitably threaten the future of the community. The use of drug use not only happen to adults but also adolescents and children. Dumolodo and Ipilo are villages located between 12 (twelve) villages in the Gentuma Raya Sub-District. Like other villages, the population of Dumolodo and Ipilo villages is dominated by children and adolescents who are prone to drug abuse (narcotics, alcohol, psychotropics and other addictive substances). In addition, Gentuma Raya Sub-district is a Trans Sulawesi road, of course, it is an area that is prone for narcotics to be spread. The Desa Bersinar (Bersih Narkoba) Community Service Program aims to build cooperation and synergy with the North Gorontalo Government to empower the community in P4GN efforts (Prevention, Eradication, Abuse, and Illicit Trafficking of Drugs) through the program of